Extrafamilial stressors in families of transgender adolescents referred for gender-affirming medical care: a mixed-methods analysis - Douglas, Laura; Pullen Sansfaçon, Annie; Daigneault, Mathé-Manuel; Speechley, Kathy Nixon; Sanders, Emily; Bauer, Greta R. (International Journal of LGBTQ+ Youth Studies, 2025)
Transgender and nonbinary (TNB) adolescents and their families often experience trans-specific, extrafamilial stressors, which may increase when adolescents come out and try to access gender-affirming medical care. While studies have described such stressors, it is unclear whether distinct underlying patterns of stressor experiences exist, shaping family experience. 159 adolescent-parent dyads attending an initial hormone appointment for gender-affirming medical care at any of 10 clinics in Canada reported on trans-specific, extrafamilial stressor experiences in Trans Youth CAN! Latent class analysis (LCA) assessed underlying patterns; parent and family characteristics were then described for each stressor class in the final model. LCA interpretation was supplemented with thematic analysis of qualitative interviews with 36 parents at 3 of the clinics from the Stories of Care study. The optimal model had four stressor classes: "Low Disruption, Some Advocacy" (estimated 30.4%); "Some Disruption, Some Advocacy" (9.8%); "Low Disruption, Low Advocacy" (55.7%); and "Major Disruption, High Advocacy" (4.1%). Family characteristics suggested a heterogeneous sample, with differing proportions of sociodemographic and family characteristics across stressor classes. Quotations from parent interviews in Stories of Care supported the four-class stressor model. Families of TNB adolescents accessing gender-affirming medical care may experience trans-specific, extrafamilial stressors according to four latent class groupings.